2015
DOI: 10.1002/jsfa.7388
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-physiological evaluation of tomato genotypes under high temperature stress conditions

Abstract: It was concluded that the studied attributes were genotype dependent, and significant diverse performance was noted. The findings of this study pave the way towards the selection of tolerant genotypes, not only for use under high-temperature conditions but also to employ them in breeding programs to produce heat-tolerant hybrids. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 31 publications
1
18
0
1
Order By: Relevance
“…The phytoremediation potential of plants may also be enhanced by strengthening plants to tolerate heavy-metal stress and toxicity. Application of salicylic acid (SA), has been found effective to alleviate metal stress in the plant, resulting in enhanced phytoremediation potential of plants [80,81].…”
Section: Chemical Assisted Phytoremediationmentioning
confidence: 99%
“…The phytoremediation potential of plants may also be enhanced by strengthening plants to tolerate heavy-metal stress and toxicity. Application of salicylic acid (SA), has been found effective to alleviate metal stress in the plant, resulting in enhanced phytoremediation potential of plants [80,81].…”
Section: Chemical Assisted Phytoremediationmentioning
confidence: 99%
“…There is a growing interest in screening cultivated and wild tomato genetic resources to identify heat tolerant genotypes, e.g., [19][20][21][22][23]. In addition, the genetic architecture of some traits associated with heat tolerance (e.g., pollen viability, inflorescence number, pollen number, style protrusion and style length, fruit set) has been dissected and their associated quantitative trait loci (QTL) were mapped [20,24].…”
Section: Introductionmentioning
confidence: 99%
“…In tomato, heat stress causes reduced yields because of failure to set fruit and reduced photosynthetic capacity (Peet et al, 1998;Zhang et al, 2011Zhang et al, , 2012. Hightemperature stress has been reported to affect many physiologic traits, including fresh plant weight, dry weight, and leaf area in tomato (Shaheen et al, 2016;Zhou et al, 2017). Other vegetative effects include reduced photosynthetic efficiency (Bartsur et al, 1985;Criddle et al, 1997), reduced assimilate translocation, reduced mesophyll resistance, and enhanced disorganization of cellular organs (Chen et al, 1982).…”
mentioning
confidence: 99%
“…Elsewhere, it is reported that only the heat-susceptible lines exhibit the heat stress-induced physiologic perturbations during strong, acute heat stress, which suggests that heat-tolerant lines may also exhibit a greater sort of ''buffering'' capacity for heat before their systems are disrupted (Camejo et al, 2005(Camejo et al, , 2006(Camejo et al, , 2007. Selections from a wide genetic variation have been reported by Shaheen et al (2016), and molecular characterization would provide further insight into the detailed investigation on the molecular mechanism of heat tolerance in tomato.…”
mentioning
confidence: 99%